Alessandro Baricco’s infinite tales - Lanslots, Inge (Spunti e Ricerche, 2016)
In the literary production of Alessandro Baricco there is a strong tendency to suspend the regular flow of time in the narrated story: time seems to become infinite. A closer examination of the notion of time elucidates its relationship with infinity and the implications where narrative time is concerned. This will be preceded by a brief introduction of the author and his work.